COMPARISON OF RECOVERY AT EXTUBATION IN SUPINE VERSUS SEMI-FOWLER'S POSITION IN PATIENTS UNDERGOING OPEN CHOLECYSTECTOMY UNDER GENERAL ANESTHESIA (The Research of Medical Science Review, 2025)
Background: Recovery at extubation is crucial for patients undergoing open cholecystectomy under general anesthesia. While traditional supine positioning may cause discomfort, the semi-Fowler's position offers potential benefits. However, data on this comparison—particularly regarding the Bruggemann Comfort Score—are scarce. This study aimed to evaluate these positions in a local population.Objective: To compare the recovery of patients emerging from anesthesia by evaluating the mean comfort scores when extubated in the supine position versus the semi-Fowler's position.Duration: 4th February 2025 to 3rd May 2025.Methodology: A total of 152 patients undergoing open cholecystectomy were enrolled after ethical approval and informed consent. They were randomly assigned to Group A (supine) or Group B (semi-Fowler’s) using a lottery method. Standard anesthesia was administered, and the Bruggemann Comfort Score was assessed immediately after extubation.Results: 152 patients (mean age 39.62 ± 13.87 years) participated in the study. Group A had significantly higher heart rate, systolic blood pressure, and respiratory rate at extubation, indicating a more stressful recovery. Group B demonstrated better oxygen saturation and significantly higher Bruggemann Comfort Scores (2.49 ± 0.81 vs. 1.93 ± 0.91, p = 0.000), suggesting improved comfort and a smoother recovery process. Conclusion: Patients extubated in the semi-Fowler’s position showed better recovery, with more stable vital signs and higher Bruggemann Comfort Scores. Although superiority was consistent across subgroups, statistical significance was lacking in some, likely due to small sample sizes. The semi-Fowler’s position appears to enhance extubation outcomes after open cholecystectomy.